BIOGRAPHY, HISTORY, AND MEMORY ABOUT SOME IMPERIAL FIGURES. - BENOIST, STÉPHANE (Bulletin of the Institute of Classical Studies, 2017)
This is a paper about some imperial figures, and mainly the first emperor, Augustus, through the reception of his persona during the first four centuries of the Principate. In three sections, a few aspects of a Roman perception of history are developed through various uses of autobiography, biography, and historical narratives about emperors, from the very beginnings to the reception, from the Antonines to the Theodosians, of model portraits of emperors. The imperial history was made of personal itineraries and biographies, in a 'republican' staging: the permanence of a 'Populus Romanus' attending, if not participating in, political rituals, the imperial eloquentia frequently celebrated by imperial biographers and used in traditional contiones, the monumental setting of politics - the central function of the forum and many other localities of a city 'full of memories'. The very inspiring contributions offered by the books and articles Fergus Millar has dedicated to a 'Greco-Roman' world considered as widely as possible are used as a guide throughout this essay.